A Tribute to Robert (Bob) Sim-Personal Memories of Working in Bob's Lab - Williams, Samantha; Steinkasserer, Alexander (Viruses, 2021)
This article is intended as a tribute to Robert B. Sim through the sharing of personal memories and anecdotes from two of Bob's lab members who worked in his lab between 1989 to 1994.
CRIS-Team Scopus Importer:2021-10-29
Keywords: complement; obituary; Robert B. Sim